Success and creativity in scientific research : amaze your friends and surprise yourself - Sholl, David S. (Boca Raton, FL : CRC Press, 2021)
"Long-term success in scientific research requires skills that go well beyond technical prowess. This book is aimed at students and early career professionals who want to achieve the satisfaction of performing creative and impactful research in any area of science or engineering. Both entertaining and thought-provoking, this essential work supports advanced students and early career professionals across a variety of technical disciplines to thrive as successful and innovative researchers"--
OCLC-licensed vendor bibliographic record.
Keywords: Research; Research -- Methodology; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Research & Methodology